Value contradictions in personal axiogenesis - Halian Ihor Mykhailovych (Insight: the psychological dimensions of society, 2022)
The purpose of the publication is to analyze the essence of contradictions in the system of personal values at the initial stages of one’s professional formation. Methods. Both the value preferences and value contradictions of an individual were studied using the method of O. Fantalova “The level of correlation between “value” and “accessibility” in various life spheres” modified (keeping basic values) for our study. Results. The study involved 110 first-year students of higher education institutions having various specializations. The research methodology was based on the vision of personality as an open and dynamic system that self-organizes and self-develops. Its functional characteristics are meanings and values as backbone components of personality. The value preferences of young people were analyzed in terms of median indicators of the importance of value, its experience, and striving for implementation. Contradictions in the systems of students’ value orientations were established. The level of individual self-actualization is fundamental for the depth of experiencing value contradictions. Conclusions. The value system of students is aimed at achieving their goals and self-actualization. Contradictions in the personal axiological system are caused by the lack of structuring in its subsystems. Structuring criteria comprise the significance of value, the degree of its experience by an individual and readiness for its implementation. We believe that the depth of value contradictions is related to personal self-actualization. We assume that the higher the level of self-actualization, the less the depth of experiencing value contradictions, and vice versa. Analysis of particularities of contradictions in the axiosystem can contribute to the establishment of a basis for personal development focused on maximum self-actualization. Studying the intrinsic value core in young people at the initial stage of their professional development and in a situation of complexity and uncertainty seems promising.